Global well-posedness for some fluid models - Qin, Yuming (EDP Sciences, 2023)
This book presents recent results on global well-posedness including asymptotic behavior of global solutions to some fluid models, such as combustion model of radiative gas, radiation hydrodynamics model, Navier-Stokes equations with capillary and p-th power Newtonian fluid model. These models have the similar structures, which consist of Navier-Stokes equations coupled with other equation or with other effects. Results collected in this book are established by the authors and their collaborators in recent years
Keywords: MATHEMATICS / Differential Equations / Partial